Upaya Meningkatkan Kemampuan Berbahasa Melalui Metode Bermain Kartu Huruf - Maria Yustina Nggera Ngaba; Kadek Suartini; Luh Srinadi; Putu Adi Kristiani (Universitas Nusa Cendana, 2021)
This report was made based on the background of problems that occurred in the B1 group of St. Joseph Kindergarten, namely the low language ability of children in recognizing and arranging letters into a word. To overcome this problem, researchers designed a learning process through letter card playing activities with the aim of improving the language skills of group B1 children in St. Joseph Kindergarten which amounted to 15 children consisting of 5 boys and 10 girls. The design of this research activity refers to the flow of Classroom Action Research which is divided into 2 cycles and 4 stages, namely planning, implementation, observation and reflection. Data in this action research is also collected by observation, assignment and documentation. Based on the results of the data analysis collected, it is proven that through playing letter cards can improve the language skills of group B1 children in St. Joseph's Kindergarten. With the results of development achievements as follows: in cycle I children who are in the stage of Very Good Development (BSB) as much as 13% and increase in cycle II to 60%.